Jennwenomyces guizhouensis sp. nov. from a freshwater habitat in Guizhou, China - Xiong, Dan; Ou, Jing; Chen, Ya-Ya (Phytotaxa, 2025)
During a study on hyphomycetous fungi, two isolates were obtained from submerged decaying wood in Guizhou Province, China. Based on phylogenetic analysis of combined LSU and ITS sequence data and detailed morphological comparisons with other asexual species within Junewangiaceae, a new species, Jennwenomyces guizhouensis, is introduced. This species is characterized by its navicular or obclavate to cylindro-clavate conidia and unique phylogenetic position. Both morphological data and molecular analyses support its taxonomic placement. A description, illustrations, and phylogenetic analysis results of the new species are provided. Notably, J. guizhouensis represents the second reported lignicolous asexual species from a freshwater habitat in China, expanding our understanding of fungal diversity in aquatic ecosystems.